Perbandingan Praktik Manajemen Kredit dalam Mencegah Kredit Macet pada Koperasi Murah Hati dan Koperasi Patuh Karya di Kabupaten Lombok Timur - Nadila Afriliana; Muhammad Zainul Majdi; Pahrudin Pahrudin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study is motivated by the importance of effective credit management in ensuring the sustainability of savings and loan cooperatives, particularly in reducing non-performing loans. Differences in credit management practices across cooperatives represent a relevant issue, especially in balancing formal system-based approaches and trust-based social mechanisms. This study aims to analyze and compare credit management practices in preventing loan defaults at Koperasi Murah Hati and Koperasi Patuh Karya in East Lombok Regency. A qualitative approach with a comparative design was employed. Data were collected through in-depth interviews, observation, and documentation involving cooperative management and borrowing members, and analyzed using data reduction, comparative tabulation, and descriptive-analytical interpretation. The findings reveal that Koperasi Murah Hati applies a trust-based approach characterized by simplified procedures without collateral and field verification, while Koperasi Patuh Karya implements a more formal system through administrative verification, feasibility assessment, and collateral requirements. However, Koperasi Murah Hati shows a lower non-performing loan rate (3.7%) compared to Koperasi Patuh Karya (10.5%). These findings indicate that effective credit management is influenced not only by formal systems but also by social factors such as trust and communication.